Analyst the Investor Intention on Socially Responsible Investment in Batam Using the Theory Of Planned Behavior Moderated by Religion - Yandi suprapto; Wirren Chang; Hesniati (LPPM Universitas Negeri Jakarta, 2024)
This study aims to study the investors intention to invest on socially responsible investment (SRI) using a theory called the planned behavior theory, the main research for this study consist of attitude, environmental attitude, social self-efficacy, and subjective norm moderate by religion. In this study, cross sectional data collected using a self-managed questionnaire by looking at several references from previous studies which then been made via Google form and distributed randomly to investors in Batam for 5 months. The sample uses